Pengaruh laju aliran udara dan lubang uap air terhadap kinerja kompor dengan bahan bakar oli bekas - Mafruddin Mafruddin; Kemas Ridhuan; Eko Budiyanto; Kurniawan Kurniawan; Muhammad Atiq Mubarak; Neta Bagus Pratama (Universitas Muhammadiyah Metro, 2022)
Oil waste produced from motor vehicle lubricants can pollute the environment. One alternative that can be done to prevent environmental pollution is by utilizing waste oil as fuel. Several factors can affect the temperature and quality of combustion, namely the air flow rate and the addition of water vapor in the combustion process. The purpose of this study was to determine the effect of the air flow rate and the number of steam holes on the temperature and efficiency of the stove with used oil fuel. The research method used was experimental by making and testing stoves with waste oil as fuel and adding water vapor to maximize combustion results. Variations in the air flow rate are 9 m/s, 10 m/s, and 11 m/s and variations in the number of water vapor holes are 8, 9 and 10 pieces. From the research results, it was found that the air flow rate and the number of holes had an effect on the flame, temperature and quality of combustion. The highest temperature is 605.6â„ƒ and the highest stove efficiency is 10.91% obtained with an air flow rate of 10 m/s and 10 steam holes.